PO68 | Whole blood hypercoagulable profiles in a patient with markedly elevated lipoprotein(A) plasma levels and thrombotic complications: a case report (Bleeding, Thrombosis and Vascular Biology)
Background: Lipoprotein(a) (Lp(a)) is a well-established, genetically determined risk factor for atherosclerotic cardiovascular disease (ASCVD). It is an LDL-like lipoprotein with proatherogenic, proinflammatory, and potentially prothrombotic properties, that contributes to endothelial dysfunction, plaque formation, and thrombosis. Its distinctive component, apolipoprotein(a) is structurally homologous to plasminogen, and may impair fibrinolysis and platelet reactivity. Traditional coagulation tests are unable to identify the prothrombotic phenotype in patients with markedly elevated Lp(a) plasma levels. The possible role of whole blood rotational thromboelastometry and impedance aggregometry to evaluate hemostatic system functions in these patients is unknown.